Abnormal pulmonary lymphatic flow in patients with paediatric pulmonary lymphatic disorders: Diagnosis and treatment. (November 2020) - Itkin, Maxim; Chidekel, Aaron; Ryan, Kelly A.; Rabinowitz, Deborah
Abstract: Pulmonary lymphatic disorders are characterized by the presence of the abnormal lymphatic tissues in the thoracic cavity, presenting clinically as chylothorax, chylopericardium, chyloptysis, interstitial lung disease and plastic bronchitis. These conditions include: neonatal chylothorax, cardiac and non-cardiac plastic bronchitis, non-traumatic chylothorax, post congenital cardiac surgery chylothorax and complex lymphatic malformations. Recently developed lymphatic imaging techniques, such as intranodal lymphangiography and dynamic contrast enhanced magnetic resonance lymphangiography demonstrated abnormal pulmonary lymphatic flow from thoracic duct into pulmonary parenchyma as a pathophysiological mechanism of these diseases. Novel minimally invasive lymphatic interventions, such as thoracic duct embolization, interstitial lymphatic embolization and surgical lympho-venous anastomosis, provide an effective treatment of these conditions.